The Ottoman Red Crescent in War and Aid: Archival Insights from the Italo-Ottoman Conflict - SALMI , Aicha; Megnouche , Karim; Ould boussiafa, Rchid (The Algerian Historical Journal, 2026)
This study examines the significant contributions of the Ottoman Red Crescent Society during the Italo-Turkish War (1911-1912), a pivotal period in the decline of the Ottoman Empire. Using archival documents, the study reveals how, despite significant political, military, and logistical challenges, including financial difficulties, a shortage of medical personnel, the Society was able to deliver vital humanitarian aid to both military personnel and civilians. In addition to its work as a relief organization, it served as a tactical extension of the Empire, providing a covert means of bolstering its military presence under the guise of humanitarian aid. By establishing hospitals and securing global support